Learning Beyond Textbooks: How Mothers’ Education and Job Status Shape Gender Stereotypes - Talmeez Fatma Naqvi; Naushad Husain (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
The present study investigates the levels of gender stereotyping among prospective teachers and examines the influence of maternal education and job status, along with the students’ gender and locality, on their gender-role attitudes. A descriptive survey design was employed on a sample of 147 graduate and postgraduate students from teacher education institutions of Bhopal, India. Data were collected using a standardized Gender Stereotypes Scale. Findings revealed that a slightly less than three-fourth of respondents held average gender stereotypes, and nearly one-fourth displayed low stereotypes. Findings revealed that higher maternal education was inversely associated with gender stereotyping, with the lowest stereotypes found among students whose mothers were postgraduates. Working mothers were also linked to lower gender stereotype scores compared to homemakers. Regression analysis confirmed that maternal education, locality, and student gender significantly predicted gender stereotype scores, collectively explaining one-third of the variance. The results highlight the pivotal role of maternal factors, especially education, in shaping egalitarian attitudes in future educators. Implications for teacher education and gender sensitization programs are discussed.